Case report: Visual snow as the presenting symptom in multiple evanescent white dot syndrome. Two case reports and literature review - Hang, Chenyue; Yan, Yan (Frontiers in Neurology, 2022)
Purpose Multiple evanescent white dot syndrome (MEWDS) usually manifests as photopsia, enlarged blind spots, scotomas, and blurred vision, which can be classified into positive and negative visual phenomena. Visual snow and chromatopsia were rarely reported in these patients. Herein, we described two Chinese female patients with MEWDS who initially presented with visual snow, and one of them also had yellow-tinged vision. Methods First, we performed the chart review of two patients. Second, we reviewed the English literature for all cases of MEWDS through PubMed until December 2021, using the terms “MEWDS” or “multiple evanescent white dot syndrome.” We concluded on all the reported patients' demographic features and symptoms. The visual acuity of patients with/without positive or negative visual phenomena was compared through one-way ANOVA. Results Patient 1: A 27-year-old Chinese woman experienced continuous visual snow and yellow-tinged vision in the right eye for a week. She noticed tiny white and black dots involving the entire visual field and shimmering light inferiorly. Patient 2: A 22-year-old Chinese woman complained of a gray area with continuous visual snow in the temporal visual field of the left eye for 5 days. The ocular examinations, including fundus autofluorescence (FAF), optical coherence tomography (OCT), and indocyanine green angiography (ICGA), confirmed the diagnosis of MEWDS. Their symptoms resolved spontaneously without treatment. We found 60 MEWDS case reports (147 cases) in PubMed. The mean age was 31.2 years old. The mean LogMAR best-corrected visual acuity was 0.35 ± 0.39 at the first visit and 0.01 ± 0.16 at the last visit. The most common symptoms included blurred vision (72.8%), enlarged blind spot (42.2%), photopsia (37.4%), and scotoma (33.3%). We found the patients with only positive visual phenomena had significantly worse visual acuity at the first and last visit than patients with only negative visual phenomena (p = 0.008) or the patients with both positive and negative visual phenomena (p = 0.026). Four cases similar to visual snow were discovered. Compared to the MEWDS patients without visual snow, the patients with visual snow tend to have a larger proportion of females (p = 0.005) and a better visual acuity at the first visit (p = 0.007). Conclusion Herein, we expand upon the clinical manifestations of MEWDS with visual snow, and the symptoms attributable to visual snow could precede the onset of MEWDS. Neurologists and ophthalmologists should carefully rule out occult chorioretinopathy before diagnosing visual snow syndrome.